2006
DOI: 10.1542/peds.2006-0913k
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Case-Study Results of Potentially Better Practices for Staffing in Neonatal Intensive Care Units

Abstract: OBJECTIVE. Five NICUs that participate in the Vermont Oxford Network Quality Improvement Collaborative have implemented several potentially better practices in an attempt to decrease nurse turnover by 50%. These potentially better practices focus on orientation, rewards and recognition, healthy work environment, nurse-physician collaboration, and nursing autonomy.METHODS. Each unit implemented some or all of the potentially better practices. An Excel spreadsheet tool for tracking turnover rates was developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
7
0
4
Order By: Relevance
“…Experience in implementing these PBPs is the subject of a companion article. 28 Other challenges are the broader organizational characteristics beyond the NICU that affect turnover, such as pay, benefits, and location of the hospital. It is important to track these variables to determine the impact that they have on staff who leave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience in implementing these PBPs is the subject of a companion article. 28 Other challenges are the broader organizational characteristics beyond the NICU that affect turnover, such as pay, benefits, and location of the hospital. It is important to track these variables to determine the impact that they have on staff who leave.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 73% of physicians rated collaboration and communication with nurses as high or very high. A companion article 28 describes a tool that was developed by the STARS group to expose these differences in mental models. By gaining an understanding of these discrepant attitudes, concrete interventions can be used.…”
Section: Pbp 4: Improve Nurse-physician Collaboration In the Nicumentioning
confidence: 99%
“…A similar strategy was used for identifying stakeholders who might facilitate or inhibit adoption. Although nurse–physician collaboration influences EBP adoption in hospital settings (Schmalenberg et al 2005; Rikli et al 2006), this relationship typically does not apply to school nurses in the US. Various stakeholder groups (e.g., school administrators) that are present in the school setting, and may exert a similar influence, were substituted.…”
Section: Methodsmentioning
confidence: 99%
“…(2008) found that after participating in the creation of changes and implementing them, nurses reported increased perceptions of their work and their work environment. When staff created and implemented potentially better practices (PBPs) in five Neonatal Intensive Care Units because of high turnover, the turnover rates decreased anywhere from 13 to 64% (Rikli et al. 2006).…”
Section: Retentionmentioning
confidence: 99%